2014
DOI: 10.1589/jpts.26.797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task-oriented Approach on Affected Arm Function in Children with Spastic Hemiplegia Due to Cerebral Palsy

Abstract: [Purpose] The purpose of the present study was to examine the effects of task-oriented approach on motor function of the affected arm in children with spastic hemiplegia due to cerebral palsy. [Subjects] Twelve children were recruited by convenience sampling from 2 local rehabilitation centers. The present study utilized a one-group pretest-posttest design. All of children received task-oriented training for 6 weeks (40 min/day, 5 days/week) and also underwent regular occupational therapy. Three clinical tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…The task-oriented approach used in the present study includes problem solving and functional tasks 7 ) . A number of recent studies have demonstrated the effects of task-oriented approaches 8 , 9 , 10 ) . However, only a few studies have applied a step-by-step task training program composed of ADL that the patient wants to accomplish.…”
Section: Introductionmentioning
confidence: 99%
“…The task-oriented approach used in the present study includes problem solving and functional tasks 7 ) . A number of recent studies have demonstrated the effects of task-oriented approaches 8 , 9 , 10 ) . However, only a few studies have applied a step-by-step task training program composed of ADL that the patient wants to accomplish.…”
Section: Introductionmentioning
confidence: 99%
“…Children suffering from spastic hemiplegia generally experience various motor and sensory impairments, such as muscle weakness, spasticity, abnormal movements, and sensory dysfunctions, and approximately 50% show greater disability in the upper extremities than the lower ones. Dysfunctions in the upper extremity result in these patients being dependent on others to perform daily activities and leads to a lack of successful social integration (34, 35). The effect of HAL-SJ seen in this study may also apply to hemiplegia CP and may be useful to improve their ADL.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one study demonstrates children with CP who play interactive videogames for 3 weeks show improvements in balance and motor performance 25 ) . Children with CP may have impaired postural balance, which contributes to gait abnormalities 26 , 27 ) . Furthermore, loaded sit-to-stand exercises improve basic motor abilities, functional muscle strength, and walking efficiency 28 , 29 , 30 ) .…”
Section: Discussionmentioning
confidence: 99%